P35 A collaborative approach to controlling an HIV outbreak among intravenous drug users. (23rd May 2012) - Bell, G; Devey, T; Cope, A; Evans, C; Hughes, C; Naylor, S; Greig, J M; Tunbridge, A J; Lagundoye, O; McNaught, R
Abstract : Background: In 2008 an intravenous drug user (IVDU) admitted to the infectious diseases unit was diagnosed with late-stage HIV. He named five injecting partners, of whom three tested negative for HIV, one refused, and one was untraced. In early 2010 another IVDU was diagnosed, naming two injecting partners of the previous case who had either declined or tested negative in 2008. Objective: To control an outbreak of HIV among IVDUs Interventions: A multidisciplinary outbreak control team was convened in 2008 and 2010 with representation from the Health Protection Unit, the Drug and Alcohol Action Team, Genitourinary Medicine, Infectious Diseases, and Virology to develop a control strategy. Traditional partner notification was supplemented by cluster testing among associates in housing projects and drop in centres used by IVDUs. Opportunistic screening of IVDUs attending health services was promoted. Laboratory investigations included phylogenetic analysis and the recent infection testing algorithm. Outcomes: A further 6 cases were identified in 2010: two through hospital screening and four through partner notification. Cluster testing did not yield any further cases among associates (0/29), but presented an opportunity to raise awareness of local HIV risk among IVDUs. Joint working between services was a feature of all interventions. All 8 cases 2008–2010 are the same strain, and 7/8 are linked to at least one other case. Despite extended surveillance at centres providing treatment for substance misuse, no further new cases have been identified since September 2010. Conclusion: An HIV outbreak among a hard-to-reach population has been successfully controlled by a prompt and close collaboration between services to deliver a range of complementary control strategies. We remain vigilant to the possibility of further cases since the source of one case has not been identified.